Translation of two healthy eating and active living support programs for parents of 2–6 year old children: a parallel partially randomised preference trial protocol (the ‘time for healthy habits’ trial) - Megan L. Hammersley; Rebecca J. Wyse; Rachel A. Jones; Luke Wolfenden; Serene Yoong; Fiona Stacey; Simon Eckermann; Anthony D. Okely; Christine Innes-Hughes; Vincy Li; Amanda Green; Christine May; et al. (BMC Public Health, 2020)
Abstract Background Parents are key decision makers and role models in establishing and maintaining healthy behaviours in their children. Interventions involving parents have been shown to be more effective than those that do not, but there are barriers to participation. Efficacy trials have previously been conducted on two such parent-focussed healthy eating and active living interventions with the potential to overcome these barriers - Healthy Habits (telephone-based) and Time2bHealthy (online) with promising results. Further research is now required to determine the effectiveness of these interventions in a real-world context. The Time for Healthy Habits study is a 3-arm partially randomised preference trial which aims to evaluate the effectiveness and cost-effectiveness of two theory-based programs to promote healthy eating and appropriate levels of movement behaviours (physical activity, sedentary behaviour and sleep) for parents of 2- to 6-year-old children (Healthy Habits Plus telephone-based program and Time2bHealthy online program), when compared to a comparison group receiving written materials. Methods Participants will be recruited across five Local Health Districts in New South Wales, Australia. The partially randomised preference design initially allows for participants to decide if they wish to be randomised or opt to select their preferred intervention and has been recommended for use to test effectiveness in a real-world setting. Both interventions incorporate multiple behaviour change techniques and support parents to improve their children’s healthy eating, and movement behaviours (physical activity, sedentary behaviour and sleep) and run for 12 weeks, followed by a 3-month and 9-month post-baseline follow-up. Participants will also be asked to complete a process evaluation questionnaire at the completion of the intervention (3-months post-baseline). Outcomes include fruit and vegetable intake (primary outcome), non-core food intake, weight status, physical activity, sedentary behaviour, and sleep habits. Discussion To our knowledge, this is the first translational research trial evaluating the effectiveness and cost-effectiveness of a healthy eating and active living intervention in the 2- to 6-years age group. The results will build the evidence base in regard to translation of effective childhood obesity prevention interventions and inform the implementation and delivery of community based childhood obesity prevention programs. Trial registration UTN: U1111–1228-9748, ACTRN: 12619000396123p .